Analisis Proses Kreatif Komunitas Artnonymous Visual Dalam Penciptaan Karya Mural Di Cianjur - Akhmad Baehaqi, Faiq; Cahyana, Agus; Nagara, Martien Roos; Falah, Asep Miftahul (Studi Budaya Nusantara, 2024)
Murals, a form of artistic expression that emphasizes creativity in painting on large, expansive, and permanent media such as building walls, fences, streets, and other surfaces. Murals serve as the primary outlet for artists to convey their ideas using various types of paint such as spray paint, water-based paint, or oil paint. The aim of this research is to explore the factors underlying the creative ideas acquisition within the Artnonymous Visual community, referencing Graham Wallas' theory comprising stages of preparation, incubation, illumination, and verification. Additionally, the study aims to deeply understand the process of mural creation undertaken by the Artnonymous Visual community and to analyze the level of creativity in their mural works in Cianjur. The research methodology employed is qualitative descriptive, enabling researchers to describe, analyze, and depict phenomena and events occurring in the context of mural art creation. Murals created by the Artnonymous Visual community feature themes centered around animals and their lives, designed to allow local residents and pedestrians to interact directly with the artwork, fostering profound visual and social experiences in public spaces. This study is expected to significantly contribute to understanding the creative process in mural art and the importance of interaction between artwork and society. The findings aim to provide valuable insights for the development of local visual culture and to inspire mural art practitioners in various community settings.